Pareto Optimal Reconfiguration of Power Distribution Systems with Load Uncertainty and Recloser Placement Simultaneousely Using a Genetic Algorithm Based on NSGA-II - Sina Khajeh Ahmad Attari; Mahmoud rReza Shakarami; Farhad Namdari (Institute of Advanced Engineering and Science, 2016)
Reconfiguration, by exchanging the functional links between the elements of the system, represents one of the most important measures which can improve the operational performance of a distribution system. Besides, reclosers use to eliminate transient faults, faults isolation, network management and enhance reliability to reduce customer outages. For load uncertainty a new method based on probabilistic interval arithmetic approach is used to incorporate uncertainty in load demand that can forecast reasonably accurate operational conditions of radial system distribution (RDS) with better computational efficiency. In this paper, the optimization process is performed by considering power loss reduction along with reliability index as objective functions. Simulation results on radial 33 buses test system indicates that simultaneous optimization of these two issues has significant impact on system performance.